Implementasi Kebijakan Rehabilitasi Rumah Tidak Layak Huni Menjadi Layak Huni di Kabupaten Pasaman Barat - Roni Wulansari; Karjuni Dt Ma'ani (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This study aims to determine the implementation of the policy of rehabilitating uninhabitable houses into habitable houses in west pasaman regency. This research was motivated by the seriousness of the government in meeting the basic needs of housing through improving the quality of houses, the problems raised were related to budget constraints and lack of socialization by the organizers to the community. To answer this problem, interviews were conducted with 5 sources. This research was conducted at the housing and settlement service of west pasaman regency. The tools used for data analysis were qualitative. According to the results of interviews conducted, the implementation of the rehabilitation policy for unfit for habitation in west pasaman regency has been implemented during 2017-2019 and continues until 2025. The number of houses that have been rehabilitated based on the decree of the regent of west Pasaman Regency is 475 housing units.